Locative literature: experiences with the textopia system. (1st January 2011) - Løvlie, Anders Sundnes
This paper presents the textopia project, a locative media design experiment set up to explore the relationship between places and literary texts. The system allows a user to walk through a city and listen to texts that talk about the places the user is passing by, thus making possible a new way of experiencing place-bound literature in relation to place. The system also allows any user to write and share their own texts connected with places, exploring what it is to write locative literature. The sharing of old texts and usergenerated texts through the system is analysed and used to outline some categories of locative literature, unified under the concept of 'poetically augmented reality'.